Studiensammlung “Antique Lapidarium” in the Restoration and Storage Center “Staraya Derevnya” as an Example of Epigraphic Texts Exposure - Eremeeva, Anna A. (Actual Problems of Theory and History of Art, 2022)
Studiensammlung is a phenomenon originating from the Classicist European tradition of creating open storages of pieces of art and scientific materials available at museums and universities as visual aids for students, scholars and collectors. Such collections have not lost their relevance today, as evidenced by their popularity at the Römisch-Germanisches Museum at Cologne, the University of Vienna, the British Museum and many others.Studiensammlung of the Hermitage Department of Greek and Roman Antiquities was opened for visitors at the Restoration and Storage Center “Staraya Derevnya” in 2015. About ninety epigraphic texts from archaeological sites in the Northern Black Sea region which were excavated in the 19th–20th centuries are presented here. The chronology of materials exhibited in the open storage “Antique Lapidarium” covers nine hundred years of Ancient Greek epigraphy: from the 6th century BC to the 3rd century AD. Each of the documents exhibited has its own significance for the reconstruction of the history of the region.The greater part of the collection was formed by the finds from archaeological excavations of the 19th century at the ancient sites of Tanais and Gorgippia, at the edge of 19th and 20th centuries in Panticapaeum and at the dawn of the 20th century in Olbia. Plenty of the pieces were purchased at different times. For example, many Gorgippian inscriptions were bought by N. I. Veselovsky in 1908 in Anapa. Due to various historical circumstances the Hermitage funds were replenished by epigraphic monuments from private collections of the Stroganovs and N. P. Likhachev, as well as from the collections of the Academy of Fine Arts and the Leningrad Historical and Linguistic Institute. In the mid-20th century and its second half, the Nymphaeum, Berezan and Chersonese archaeological expeditions of the State Hermitage made an invaluable contribution to the funds.Latin inscriptions are presented at the exhibition, but the monuments of ancient Greek epigraphy make up its bulk. Lapidary sources, except for those that are not amenable to recovery, can be considered by category. Particularly noteworthy are proxenoi, honorary decrees and manumissions, as well as dedications to gods. In addition, in the “Ancient Lapidarium” one can find table graffiti, inscriptions on amulets, and lead letters concerning workaday topics.The conclusions about the unique character and diversity of the collection are obvious. In addition to epigraphists who study the nuances of the chronology and paleography of local versions of ancient Greek writing, the collection of inscriptions of the Department of Greek and Roman Antiquities should undoubtedly attract schoolchildren and students of specialized departments of higher educational institutions. The importance and benefits of open storage for historians and archaeologists are determined by the fact that the gallery contains a rare collection of documents, which sometimes are the only source for restoring historical events and clarifying knowledge about the state system, official religious cults in the Greek colonies of the Northern Black Sea region, about private and social life of residents of ancient cities in the region. Ancient authors did not always pay enough attention to the periphery of the Greek world, but epigraphic monuments help fill such gaps in.
Keywords: Classical antiquity; Ancient Greek inscriptions; Lapidarium; new exposition; Northern Black Sea region